1970
DOI: 10.2135/cropsci1970.0011183x001000030033x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Full‐Sib Selection1

Abstract: Reciprocal full‐sib selection is a breeding procedure for concurrent population improvement and hybrid development. Reciprocal full‐sib selection should be an efficient procedure for crop species in which non‐additive genetic effects, as well as additive, are important in the expression of hybrid superiority. Full‐sib progenies are yieldtested, and selections are made for improvement of the two parental populations. These same yield trials also are the first season of the evaluation and development of single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
11

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 0 publications
1
53
0
11
Order By: Relevance
“…Idealizado por Comstock et al (1949), como um processo de melhoramento de duas populações e do híbrido entre elas, a seleção recorrente recíproca (SRR) com famílias de meios-irmãos paternos interpopulacionais e a recombinação de progênies S 1 têm proporcionado, na maioria dos casos, resultados favoráveis -com milho e milho-pipoca -, em relação à produção, resistência a pragas e doenças, resistência ao acamamento, entre outros caracteres (Keeratinijakal & Lamkey, 1993;Rademacher et al, 1999;Butron et al, 2000). A mesma afirmação pode ser feita em relação às modificações do método realizadas por Paterniani (1967), que sugeriu o uso de famílias de meios-irmãos maternos interpopulacionais e recombinação de progênies de meios-irmãos; e por Lonnquist & Williams (1967) e Hallauer & Eberhart (1970), que propuseram o emprego de progênies de irmãos-completos interpopulacionais e recombinação de famílias S 1 , para o melhoramento das populações e do híbrido, e de famílias de irmãos-completos interpopulacionais endogâmicas, para a obtenção de híbridos de linhagens. Considera-se que o processo de SRR com irmãos-completos maximiza a seleção para capacidade específica de combinação, e favorece a obtenção de híbridos superiores de linhagens das populações envolvidas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Idealizado por Comstock et al (1949), como um processo de melhoramento de duas populações e do híbrido entre elas, a seleção recorrente recíproca (SRR) com famílias de meios-irmãos paternos interpopulacionais e a recombinação de progênies S 1 têm proporcionado, na maioria dos casos, resultados favoráveis -com milho e milho-pipoca -, em relação à produção, resistência a pragas e doenças, resistência ao acamamento, entre outros caracteres (Keeratinijakal & Lamkey, 1993;Rademacher et al, 1999;Butron et al, 2000). A mesma afirmação pode ser feita em relação às modificações do método realizadas por Paterniani (1967), que sugeriu o uso de famílias de meios-irmãos maternos interpopulacionais e recombinação de progênies de meios-irmãos; e por Lonnquist & Williams (1967) e Hallauer & Eberhart (1970), que propuseram o emprego de progênies de irmãos-completos interpopulacionais e recombinação de famílias S 1 , para o melhoramento das populações e do híbrido, e de famílias de irmãos-completos interpopulacionais endogâmicas, para a obtenção de híbridos de linhagens. Considera-se que o processo de SRR com irmãos-completos maximiza a seleção para capacidade específica de combinação, e favorece a obtenção de híbridos superiores de linhagens das populações envolvidas.…”
Section: Introductionunclassified
“…Hallauer (1984), ao trabalhar com famílias de irmãos-completos, também obteve resultados favoráveis, em sete ciclos de seleção, com as populações BS10 e BS11. A resposta direta na população híbrida foi de 2,1% por ciclo, para a produção, e as respostas correlacionadas nos parentais BS10 e BS11 foram de 2,7 e 2,4%.…”
Section: Introductionunclassified
“…This modification to the reciprocal full-sib breeding procedure was described in detail by Hallauer and Eberhart (1970). Jones et al (1971) algebraically and by computer simulation, compared reciprocal recurrent selection based on evaluation of half-sib testcrosses and the population improvement phase of reciprocal full-sib selection.…”
Section: Additional Progress From Reciprocal Full-sib Selection In Bsmentioning
confidence: 99%
“…A modification of the procedure, integrating population improvement and single-cross development was described by Hallauer and Eberhart (1970). They also suggested that the breeding method be called reciprocal full-sib selection.…”
mentioning
confidence: 99%
“…RRS is a method of half-sib selection where one population serves as tester for the reciprocal population. Another type of interpopulation Improvement, reciprocal full-sib selection (RFS), involves the evaluation of full-sib families obtained from crosses between SQ or plants from the two populations under selection (Hallauer and Eberhart, 1970). One main advantage of RFS is that, with given resources, twice as many plants from the source populations can be progeny tested compared to RRS.…”
mentioning
confidence: 99%